Financing transportation networks - Levinson, David M. (E. Elgar Pub., 2002)
An approach that creates the local winners necessary to implement road pricing is required before it can be expected to become widespread." "Economists, civil engineers, planners, students and policymakers will find this detailed examination of transportation networks enlightening and useful."--BOOK JACKET
Includes bibliographical references (p. 215-227) and index
Keywords: Routes - Finances; Routes à péage; Tolwegen; Roads -- Finance; Toll roads; Straßenbenutzungsgebühr; Verkehrsnetz; Straßenbau; Straßenverkehr; Finanzierung